Evaluation Influence: The Evaluation Event and Capital Flow in International Development. (December 2017) - Bell, David A.
Background: Assessing program effectiveness in human development is central to informing foreign aid policy-making and organizational learning. Foreign aid effectiveness discussions have increasingly given attention to the devaluing effects of aid flow volatility. This study reveals that the external evaluation event influences actor behavior, serving as a volatility-constraining tool. Method: A case study of a multidonor aid development mechanism served examining the influence of an evaluation event when considering anticipatory effects. The qualitative component used text and focus group data combined with individual interview data (organizations n = 10, including 26 individuals). Quantitative data included financial information on all 75 capital investments. The integrated theory of influence and model of alternative mechanisms used these components to identify the linkage between the evaluation event and capital flow volatility. Results: Aid approved in the year of the midterm evaluation was disbursed by the mechanism with low capital volatility. Anticipating the evaluation event influenced behavior resulting in an empirical record that program outcomes were enhanced and the mechanism was an improved organization. Implications: Formative evaluations in a development program can trigger activity as an interim process. That activity provides for a more robust assessment of ultimate consequence of interest. Anticipating an evaluation can stimulate donor reality testing . The findings inform and strengthen future research on the influence of anticipating an evaluation. Closely examining activities before, during, and shortly after the evaluation event can aid development of other systematic methods to improve understanding this phenomenon, as well as improve donor effectiveness strategies.